Morfogênese da metrópole goiana - Um estudo sobre a transição morfológica da cidade em metrópole - Oliveira, Pedro Henryque Melo de (2018)
This work has devoted itself to understanding the spatial dimension as the city becomes a metropolis, thus highlighting what is called a morphological transition. The morphological transition of the city into metropolis was understood as a result of the space-time compression process (cf. R. Hidalgo, F. Arenas and D. Santana, 2016), equivalent to the socio-spatial changes that produce a "portable city" (cf. M. Gottdiener, 1993). The central problem of the study was to try to understand how the urban form of the contemporary metropolis emerged in the city of Goiânia. Thus, the morphogenesis of the metropolis Goiânia is a study that runs through a process of spatial transformation in which the an intraurban structure and the city's growth pattern differ over time. It was sought to accompany in this morphological transition the alteration in the territory of Goiás, in which the capital leaves a condition of an urban nucleus to reach the current days as urban agglomeration, the great urban space of Goiânia. (cf. Castello Branco, 2003)